PENGARUH MODEL PEMBELAJARAN BLENDED LEARNING DALAM PEMBELAJRAN PPKN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI IPS DI SMA NEGERI 2 TONDANO - Warouw, Roland Aldo; Pangalila, Theodorus; Keintjem, Maxi Ventje (Academy of Education Journal, 2023)
The purpose of this study was to determine the effect of blended learning in civic learning on the critical thinking skills of class XI IPS students at SMA Negeri 2 Tondano. The research model used is quantitative research with the type of quasi-experimental research with the research design Pretest-Posttest Nonequivalent Control Group Design namely by using an experimental class and a control class. Based on the data obtained, the hypothesized result in this study shows that the blended learning model significantly influences the critical thinking level of students in class XI IPS at SMA Negeri 2 Tondano